2010
DOI: 10.1002/acr.20148
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiographic joint space width with magnetic resonance imaging cartilage morphometry: Analysis of longitudinal data from the osteoarthritis initiative

Abstract: Objective. Magnetic resonance imaging (MRI) and radiography are established imaging modalities for the assessment of knee osteoarthritis (OA). The objective of our study was to compare the responsiveness of radiographic joint space width (JSW) with MRI-derived measures of cartilage morphometry for OA progression in participants from the Osteoarthritis Initiative (OAI). Methods. This study examined the baseline and 12-month visits of a subset of 150 subjects from the OAI. Measurement of radiographic JSW was fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 21 publications
2
117
0
Order By: Relevance
“…A study by Duryea et al proposes measuring the joint space width (JSW) as an improved alternative to the current MR methodology for cartilage morphology. The study demonstrates that the SRM values for radiographic JSW are very much comparable to those obtained from the MRI measures and hence can be a more cost effective alternative (Duryea et al, 2010). Increasingly, studies indicate that sub regional assessment of cartilage volume/thickness is more sensitive than global assessment of longitudinal changes.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…A study by Duryea et al proposes measuring the joint space width (JSW) as an improved alternative to the current MR methodology for cartilage morphology. The study demonstrates that the SRM values for radiographic JSW are very much comparable to those obtained from the MRI measures and hence can be a more cost effective alternative (Duryea et al, 2010). Increasingly, studies indicate that sub regional assessment of cartilage volume/thickness is more sensitive than global assessment of longitudinal changes.…”
Section: Introductionmentioning
confidence: 48%
“…However, they did not find any correlation with the WOMAC score which was attributed to patients getting used to their pain (Phan et al, 2006). Several studies have utilized the longitudinal MR image data available from the Osteoarthritis Initiative (OAI) to study cartilage in OA (Eckstein et al, 2001;Duryea et al, 2010;Thompson, et al, 2010;Guermazi et al, 2011;Iranpour-Boroujeni et al, 2011;Wirth et al, 2011aWirth et al, , 2011b. Eckstein et al performed a study where they investigated the rate at which cartilage deterioration occurs when looking at OAI participants grouped in three categories described as healthy, with no radiographic evidence or risk and knees with radiographic evidence of OA (Kellgren/Lawrence score of 2-4).…”
Section: Introductionmentioning
confidence: 99%
“…Schematic of the central X-ray beam orientation when it is co-planar with the tibial plateau (green arrow) and when it is 15 deg oblique to the tibial plateau (orange arrow). measurement location in the first figure of Duryea et al (6). In the reliability testing reported on the OAI website, the intraclass correlation coefficient (ICC) for the original and repeat measurements of JSW measured at the medial 20% location was 0.987, and the limits of agreement between repeated measurements were -0.339 and 0.319 mm.…”
Section: Comparison Of Mid-coronal Plane Medial Jsn To Medial Jsn Repmentioning
confidence: 99%
“…These points are where the lateral and medial JSN is measured. Duryea et al in 2010 reported improved responsiveness of JSN measured at fixed locations [6]. An additional line is drawn that touches the caudal-most points on the medial and lateral femoral condyles.…”
Section: The Mid-coronal Plane Jns Measurementmentioning
confidence: 99%
See 1 more Smart Citation